2023
DOI: 10.1101/2023.01.17.523241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Apoptosis recognition receptors regulate skin tissue repair in mice

Abstract: Apoptosis and clearance of apoptotic cells via efferocytosis are evolutionarily conserved processes that drive tissue repair. However, the mechanisms by which recognition and clearance of apoptotic cells regulate repair are not fully understood. Here, we use single-cell RNA sequencing to provide a map of the cellular dynamics during early inflammation in mouse skin wounds. We find that apoptotic pathways and efferocytosis receptors are elevated in fibroblasts and immune cells, including resident Lyve1+ macroph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“… 135 Additionally, increasing the expression of MFG-E8 136 achieves the same therapeutic effect. Single-cell RNA sequencing has revealed that the upregulation of Axl contributes to wound closure independent of efferocytosis, 137 suggesting the involvement of other mechanisms. Interestingly, a new hybrid biomaterial composed of formyl-met-leu-phe (fMLP), FasL-conjugated silica nanoparticles (SiO2-FasL), 138 and ANXA1 N-terminal peptide Ac2-26 139 were found to successfully reduce inflammation and promote wound healing by accelerating efferocytosis to generate anti-inflammatory factors and eliminate excess neutrophils.…”
Section: Efferocytosis In Pathologies and Therapeutic Opportunities O...mentioning
confidence: 99%
“… 135 Additionally, increasing the expression of MFG-E8 136 achieves the same therapeutic effect. Single-cell RNA sequencing has revealed that the upregulation of Axl contributes to wound closure independent of efferocytosis, 137 suggesting the involvement of other mechanisms. Interestingly, a new hybrid biomaterial composed of formyl-met-leu-phe (fMLP), FasL-conjugated silica nanoparticles (SiO2-FasL), 138 and ANXA1 N-terminal peptide Ac2-26 139 were found to successfully reduce inflammation and promote wound healing by accelerating efferocytosis to generate anti-inflammatory factors and eliminate excess neutrophils.…”
Section: Efferocytosis In Pathologies and Therapeutic Opportunities O...mentioning
confidence: 99%